Analysis The Influence Of Digital Marketing, Product Differentiation, Customer Value, Service Quality To Purchase Decision And Repurchase Intention Of Millenial Generation At Shopee Online Shop - Yanti Mayasari Ginting; Alitea Moses Riski Sinaga; Raya Desmawanto Nainggolan (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract Current technological developments have changed the paradigm in shopping and fostered an online shopping system (e-commerce). Shopee is one of flatform that used to buying and selling online that provides various products to support daily activities. This study aims to determine the Influence of digital marketing, product differentiation, customer value and service quality to purchase decision and repurchase intention of millenial generation in Pekanbaru at Shopee online shop. The population in this study were all millennial generations in Pekanbaru with a sample size of 400 respondents. The method in this study uses probability sampling method and the technique used is simple random sampling technique. The technique of data analysis used multiple linear regression analysis. The results of the study concluded that the digital marketing influence purchase decision of millenial generation in Pekanbaru at Shopee online shop, product differentiation influence purchase decision of millenial generation in Pekanbaru at Shopee online shop, customer value does not influence purchase decision of millenial generation in Pekanbaru at Shopee online shop, service quality does not influence purchase decision of millenial generation in Pekanbaru at Shopee online shop, and purchase decision influence repurchase intention of millennial generation in Pekanbaru at shopee online shop. Keywords Digital Marketing, Product Differentiation, Customer Value, Service Quality, Purchase Decision and Repurchase Intention